Humerus Length Correlates with Stature among Nias Ethnic Students at HKBP Nommensen University Medan - Athalia Famelinda Gracia; Saharnauli Janna Verawaty Simorangkir; Joice Sonya Gani Panjaitan (Universitas Airlangga, Surabaya, Indonesia, 2025)
Highlights Robust statistical analyses and substantial sample size contribute to understanding anthropometric patterns and forensic medicine implications. Humerus length can be used to predict stature for the Nias tribe in North Sumatra, Indonesia. ABSTRACT Background: The identification of stature is an essential component of forensic anthropology. The measurement of stature with a single long bone of the upper limbs provided an alternative technique for estimating stature when the commonly used lower limb bone is missing. Objective: To determine the correlation between humerus length and stature among Nias ethnic students at HKBP Nommensen University, Medan, Indonesia. Materials and Methods: The study employed correlational analytics with a cross-sectional design. The study population comprises 100 active Nias ethnic students at HKBP Nommensen University, according to the inclusion and exclusion criteria, consisting of 50 males and 50 females. Sampling was done by purposive sampling. Conducting a bivariate analysis to ascertain the correlation between humerus length and stature. The linear regression analysis was conducted to derive a formula for predicting stature from humerus length. Results: The length of the male humerus bone was significantly related to stature, with a correlation coefficient of r = 0.949 (p<0.001). The length of the female humerus bone showed a significant correlation with stature, with correlation coefficients ranging from 0.783 to 0.785 (p<0.001). The precise regression equation is established according to the minimal Standard Error of the Estimate (SEE) value within each sex group. The linear regression equations obtained were the stature of males (cm) = 78.844 + 3.001 x length of left humerus (cm) and the stature of females (cm) = 19.694 + 5.189 x length of right humerus (cm). Conclusion: Among the Nias ethnic students at HKBP Nommensen University, the study discovered a strong correlation between the lengths of the right and left humerus bones and stature. As a result, stature might be calculated using a linear regression equation to measure the humerus length of the bone.